Non‐breeding areas and timing of migration in relation to weather of Scottish‐breeding common sandpipers Actitis hypoleucos. (21st January 2019) - Summers, Ron W.; de Raad, A. Louise; Bates, Brian; Etheridge, Brian; Elkins, Norman
Abstract : The number of breeding common sandpipers has declined in Britain due to poorer return rates from non‐breeding areas. To investigate little known aspects of their annual cycle, breeding common sandpipers were fitted with geolocators to track their migrations and determine their non‐breeding areas. Ten tagged birds left Scotland on 9 July (median dates and durations are given throughout the abstract). Short‐term staging was carried out by some birds in England and Ireland, then for longer by most birds in Iberia before continuing to West Africa, arriving on 28 July. Six birds spent most of the non‐breeding season (October–February) on the coast of Guinea‐Bissau, suggesting that this is a key area. Single birds occurred in Sierra Leone, Guinea, the Canary Islands and western Sahara. The southward migration from Scotland took 17.5 d (range 1.5–24 d), excluding the initial fuelling period. The first northward movement from Africa was on 12 April. Staging occurred in either Morocco, Iberia or France. Arrival in Scotland was on 2 May. The northward migration took 16 d (range 13.5–20.5 d). The main migration strategy involved short‐ and medium‐range flights, using tail‐winds in most cases. Variation in strategy was associated with departure date; birds that left later staged for shorter durations. Coastal West Africa provides two major habitats for common sandpipers: mudflats associated with mangroves and rice fields. Although the area of mangrove has been depleted, the scale of loss has probably been insufficient to account for the decline in sandpiper numbers. Rice fields are expanding, providing feeding areas for water‐birds. Meteorological data during the migrations suggest that the weather during the southward migration is unlikely to contribute to a population decline but strong cross‐winds or head‐winds during the northward migration to the breeding grounds may do so.